The influence of N-P-K fertilizer rates and cropping systems on root biomass and some root morphological variables of sweet corn and vegetable soybean - Iman, Abdulkadir; Wahab, Zakaria; Abd Halim, Mohd Ridzwan; Syed Rastan, Syed Omar (Asian Network for Scientific Information, 2006)
A field experiment using 1.2x0.5x0.5 m rhizoboxes with 280 kg soil was carried out to investigate the effect of three N-P-K fertilizer rates (50, 100 and 150% of the recommended fertilizer rate) and cropping systems (mono-crop corn or soybean, intercrop corn and soybean without root separation, with plastic and with geotextile root separation) on root biomass, volume surface area and total root length. Mono-crop corn and intercropped corn under plastic sheet root separation had significantly higher total root length than intercropped corn without root separation and with geotextile root separation, but soybean higher root volume was noticed in intercropped soybean without root separation and with geotextile root separation. Increasing fertility level from 50% of recommended rate (RFR) to 100 and 150% RFR significantly increased root dry weight of corn and soybean, as well as root volume, surface area and total root length of corn. In soybean increasing fertility level from 50 to 100% RFR increased total root length and root surface area, but further increase to 150% of recommended rate decreased both variables.